The mobilization of topics of Brazilian social thought in commercial historiography consumed in Brazil in times of democratic crisis (2013-2020) (Tempo e Argumento, 2021)
The purpose of this article is to examine the interpretations of Brazil developed in books that, evoking the generic historiographical identity, found great success in the publishing market in these years of democratic crisis. The hypothesis of the work suggests that these texts mobilized arguments produced by the authors that we learned to call “interpreters of Brazil”, who throughout the 20th century tried to inventory the causes of the Brazilian delay in synthesis essays of national history. At the end of the text, I speculate that these best-sellers of commercial historiography have collaborated to modulate political behavior in civil society in the context of the democratic crisis still underway in Brazil.Keywords: Brazilian social thinking; Sign of delay; Commercial historiography; Democratic crisis.